2005
DOI: 10.1007/11523468_113
|View full text |Cite
|
Sign up to set email alerts
|

On the Power of Random Bases in Fourier Sampling: Hidden Subgroup Problem in the Heisenberg Group

Abstract: The hidden subgroup problem (HSP) provides a unified framework to study problems of grouptheoretical nature in quantum computing such as order finding and the discrete logarithm problem. While it is known that Fourier sampling provides an efficient solution in the abelian case, not much is known for general non-abelian groups. Recently, some authors raised the question as to whether post-processing the Fourier spectrum by measuring in a random orthonormal basis helps for solving the HSP. Several negative resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Radhakrishnan et al [15] have shown Theorem 2 Let |ψ 1 , |ψ 2 be two orthogonal quantum states in C N . Then,…”
Section: Our Definition Of An Approximate (T T)-design Is As Followsmentioning
confidence: 99%
“…Radhakrishnan et al [15] have shown Theorem 2 Let |ψ 1 , |ψ 2 be two orthogonal quantum states in C N . Then,…”
Section: Our Definition Of An Approximate (T T)-design Is As Followsmentioning
confidence: 99%
“…In other words, the running time of the algorithm is poly(log p). The algorithm is particularly simple in the case r = 2, where the only nontrivial semidirect product is known as the Heisenberg group (for which it was recently shown that there is an efficient quantum algorithm whose output information theoretically determines the solution of the hsp [25]). We present the algorithm for r = 2 in Section 6.1, and then proceed to the general case in Section 6.2.…”
Section: Stripped Down Algorithmmentioning
confidence: 99%
“…If the ranks of the blocks of σ H 1 , σ H 2 are polynomially bounded, we show that r(H 1 , H 2 ) is at least polynomially large. Earlier, Radhakrishnan et al [23] had proposed a similar distance function r (H 1 , H 2 ), but it was difficult to estimate r (H 1 , H 2 ) except for very special cases. Also, the function r (H 1 , H 2 ) was not powerful enough to even show that polynomially many iterations of the random Fourier method suffice to identify a hidden subgroup in the dihedral group with high probability.…”
Section: Frobenius Distance and Ensemble State Distinctionmentioning
confidence: 99%
“…For many concrete examples of Gel'fand pair HSPs like dihedral and Heisenberg groups, the number of iterations of random Fourier sampling can be brought down to O(log |G|) by a more careful analysis. Gel'fand pairs have been studied extensively in group theory, and much recent work on the HSP has involved Gel'fand pairs, e.g., dihedral group [5,7], affine group [20], Heisenberg group [4,23], optimality of the pretty good measurement for identifying hidden subgroups from a known conjugacy class [19]. For suitable subgroups of dihedral and affine groups, it is possible to give explicit efficient measurement bases for the single register Fourier sampling procedure that identify the hidden subgroup with high probability using polynomially many copies.…”
Section: Frobenius Distance and Ensemble State Distinctionmentioning
confidence: 99%
See 1 more Smart Citation